Pengaruh "Fear of Missing Out (FOMO)" terhadap Keputusan Pembelian Impulsif pada Pengguna E-Commerce - Andre Irawan; Gita Oktarina; Revina Monalisa; Ferdi Sepri Ardiansyah; Marsyah Lie; Tadzkia Raudhatul Jannah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The rapid development of e-commerce in Indonesia has driven significant changes in consumer shopping behavior, one of which is the increasing phenomenon of impulse buying. This study aims to examine the influence of Fear of Missing Out (FOMO) on impulsive purchasing decisions among e-commerce users in Indonesia. FOMO is a psychological condition characterized by anxiety about missing out on trends, promotions, or opportunities that others are enjoying, which is further amplified by digital platform features such as flash sales, countdown timers, live broadcasts, and limited-time offers. This study used a causal associative quantitative approach involving 155 respondents who were active users of e-commerce platforms (Shopee, Tokopedia, Lazada, Bukalapak, and Blibli) selected through a purposive sampling method. Data collection was conducted through an online questionnaire using Google Forms with a 5-point Likert scale measurement instrument. Data analysis was conducted using simple linear regression using SPSS 25 and Partial Least Squares – Structural Equation Modeling (PLS-SEM) using SmartPLS 3. This research is based on two theoretical frameworks: Self-Determination Theory (SDT) and the Stimulus-Organism-Response (S-O-R) model, which collectively explain the psychological mechanisms behind impulsive buying behavior. The results are expected to provide a deeper understanding of the role of FOMO as a driver of unplanned shopping behavior in the digital era.